2021
DOI: 10.1186/s12883-021-02445-9
|View full text |Cite
|
Sign up to set email alerts
|

The protective impact of education on brain structure and function in Alzheimer’s disease

Abstract: Background The Cognitive Reserve (CR) theory posits that brains with higher reserve can cope with more cerebral damage to minimize clinical manifestations. The aim of this study was to examine the effect of education (CR proxy) on brain structure and function in Alzheimer’s disease (AD) and amnestic mild cognitive impairment (aMCI) patients and in cognitively healthy elderly (HC) individuals. Methods Fifty-seven AD patients, 57 aMCI patients and 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…The findings illustrate a consistent protective effect of education against the risk of developing AD, with a dose-dependent relationship prevailing across genders and age groups [16,17]. Similarly, in a few studies, it was underscored that education may play a pivotal role in bolstering brain reserve and fortifying cognitive coping strategies, not just in healthy individuals but also in patients diagnosed with AD [18][19][20]. Notably, Asian Americans exhibit higher education levels, potentially attributed to immigration trends and the "model minority" stereotype, reinforcing the importance of studying this group in the context of AD [21].…”
Section: Socio-demographic Characteristics and Admentioning
confidence: 75%
See 1 more Smart Citation
“…The findings illustrate a consistent protective effect of education against the risk of developing AD, with a dose-dependent relationship prevailing across genders and age groups [16,17]. Similarly, in a few studies, it was underscored that education may play a pivotal role in bolstering brain reserve and fortifying cognitive coping strategies, not just in healthy individuals but also in patients diagnosed with AD [18][19][20]. Notably, Asian Americans exhibit higher education levels, potentially attributed to immigration trends and the "model minority" stereotype, reinforcing the importance of studying this group in the context of AD [21].…”
Section: Socio-demographic Characteristics and Admentioning
confidence: 75%
“…In another study, a complex case of progressive supranuclear palsy (PSP) accompanied by depression and anxiety, was presented. The patient showed extrapyramidal symptoms and major depression, leading to impaired movement [ 19 ]. Antidepressant therapy was initiated, resulting in a reduction of depressive symptoms and somatic complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Previous explanations for this association between reduced risk for cognitive decline or dementia and a higher degree of educational obtainment hypothesised that this cognitive exertion in early-and mid-life stages might result in an increased cognitive reserve in older age. A further explanation may be that individuals with higher levels of educational obtainment may engage in mentally stimulatory activities more frequently, especially in later life stages, contributing to the preservation of cognitive function and, thus, impeding the onset of cognitive decline [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…What is more, CR has also been shown to modulate the cortical architecture, white matter macromolecular volume, and cerebral blood flow to be protective against the cognitive impairment effect in MCI patients (15)(16)(17). It has been found that MCI patients with higher CR are able to tolerate greater brain pathology such as cortical thinning or gray matter volume atrophy as well as having more severe white matter damage than patients with lower CR at a given level of cognitive impairment (18). Recent evidences have suggested that education level and higher occupational status significantly affected the relationships between hippocampal volume and executive control function, total gray matter volume and language function in MCI patients (19).…”
Section: Introductionmentioning
confidence: 99%